Study of wind–vehicle–bridge system of suspended monorail during the meeting of two trains. Issue 8 (June 2019) - Bao, Yu-long; Xiang, Huo-yue; Li, Yong-le; Yu, Chuan-jin; Wang, Yi-chao
Based on the theories of aerodynamics, bridge dynamics, and vehicle dynamics, the aerodynamic performances and the vibration characteristics of the wind–vehicle–bridge coupling system of two suspended monorail trains passing each other are analyzed. First, a wind model is presented with spectral representation method, the aerodynamic coefficients of bridge and vehicles before and after meeting are obtained through computational fluid dynamic method, and wind tunnel tests are conducted to verify the aerodynamic coefficients. Then, a vehicle dynamic model and a bridge dynamic model are established with the multi-body dynamic method and finite element method. Finally, a three-dimensional wind–vehicle–bridge coupled vibration model is established in this article using the multi-body dynamic software SIMPACK. The effects of average wind and fluctuating wind on the wind–vehicle–bridge system are studied. It is shown that the aerodynamic coefficients vary greatly under different combinations of vehicle–bridge system. The responses of the leeward vehicle change abruptly at the beginning and the end of the meeting of the two trains. And the mean wind speed has a great negative contribution to the acceleration of leeward vehicle. The lateral responses of suspended monorail vehicle are sensitive to the fluctuating wind. The roll angle of vehicle is presented for describing the running safety of the suspended monorail vehicles.